Successful Treatment of Digital Ischemia Following Carbon Dioxide Laser and Tourniquet for Digital Procedure with Adjuvant Low Level Laser therapy - Lueangarun, Suparuj; Tempark, Therdpong (Journal of Lasers in Medical Sciences, 2019)
A digital tourniquet with/without epinephrine is commonly used in local anesthetics when operating on digits. However, such a complication as digital ischemia could occur following tourniquet application. We reported an elderly patient with atherosclerotic risk factors and she subsequently underwent a digital tourniquet, partial nail plate removal, and a carbon dioxide laser treatment for subungual wart with digital gangrene development. The successful treatment consisted of wound-dressing, medication, and adjuvant low-level light therapy (LLLT) to enhance the wound healing process, thereby resulting in almost complete recovery of skin color and function of the digit in 3 months. In conclusion, the digital tourniquet should be cautiously applied, especially in elderly patients with atherothrombosis, under minimal pressure and appropriate length of time. Moreover, LLLT could be an effective adjuvant treatment to prevent the vascular complications of the digit.